2022
DOI: 10.3390/polym14102073
|View full text |Cite
|
Sign up to set email alerts
|

Confounding Effect of Wetting, Compaction, and Fouling in an Ultra-Low-Pressure Membrane Filtration: A Review

Abstract: Ultra-low-pressure membrane (ULPM) filtration has emerged as a promising decentralized water and wastewater treatment method. It has been proven effective in long-term filtration under stable flux without requiring physical or chemical cleaning, despite operating at considerably lower flux. The use of ultra-low pressure, often simply by hydrostatic force (often called gravity-driven membrane (GDM) filtration), makes it fall into the uncharted territory of common pressure-driven membrane filtration. The applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…In the case of transmembrane pressure between 2 and 70 bar, membrane compaction is considered negligible. 60 All these reasons led to set the transmembrane pressure to 4 bar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of transmembrane pressure between 2 and 70 bar, membrane compaction is considered negligible. 60 All these reasons led to set the transmembrane pressure to 4 bar.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of transmembrane pressure between 2 and 70 bar, membrane compaction is considered negligible. 60 All these reasons led to set the transmembrane pressure to 4 bar. In addition to average pore size determination, Table 3 shows contact angle, largest pore size for each membrane and theoretical LEP values calculated from aforementioned parameters.…”
Section: Water Ux Measurementmentioning
confidence: 99%
“…The phenomenon that occurs in trend A indicates compaction. With the occurrence of compaction, the permeability obtained decreases with increasing pressure received by the membrane [21], [25], [27]. At a pressure of 1 kPa the permeability of water reaches 4,090.5 (L/m 2 .hour.bar) while at a pressure of 2 kPa the permeability of water reaches 3.001 (L/m 2 .hour.bar).…”
Section: Ultra-low Pressure Filtration Performance On Campus Domestic...mentioning
confidence: 96%
“…Membrane compaction refers to changes in the physical structure of membrane materials due to transmembrane exposure. Due to the flexible nature of the polymer in the matrix, it affects the hydraulic filtration performance [27]. Compaction can occur because the membrane material is made of polymeric material, which when pressure is applied, the pores will shrink.…”
Section: Fig4 Clean Water Filtrationmentioning
confidence: 99%
“…Operation flux is an important parameter in MBR designing and operation, and it is a direct factor in polymer film fouling. Hung et al [ 14 ] reviewed recent studies on membrane compaction, wetting and fouling, demonstrating that an ultra-low-pressure membrane (ULPM) is effective for long-term filtration at stable fluxes. It has been suggested that submerged MBRs should be operated at a flux below the “critical flux”, the so-called subcritical flux, to maintain a sustainable permeability and to mitigate polymer film pollution [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%